2019
DOI: 10.20517/2394-4722.2018.71
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells, stemness markers and selected drug targeting: metastatic colorectal cancer and cyclooxygenase-2/prostaglandin E2 connection to WNT as a model system

Abstract: How to cite this article: ALHulais RA, Ralph SJ. Cancer stem cells, stemness markers and selected drug targeting: metastatic colorectal cancer and cyclooxygenase-2/prostaglandin E2 connection to WNT as a model system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 202 publications
(264 reference statements)
0
3
0
Order By: Relevance
“…Taking cancer stem cell-based model into consideration, normal stem cells act as proto-tumorigenic cells which consist of important features related to the cells which exhibit malignancy as well as indigenous start-up of important pathways essential for survival and the potential of horizonless proliferation (Fig. 3) [73]. All types of stem cells such as; pluripotent stem [76].…”
Section: Role Of Several Important Factors In the Development Of Gianmentioning
confidence: 99%
“…Taking cancer stem cell-based model into consideration, normal stem cells act as proto-tumorigenic cells which consist of important features related to the cells which exhibit malignancy as well as indigenous start-up of important pathways essential for survival and the potential of horizonless proliferation (Fig. 3) [73]. All types of stem cells such as; pluripotent stem [76].…”
Section: Role Of Several Important Factors In the Development Of Gianmentioning
confidence: 99%
“…[ 4 ] According to the Dandelion hypothesis for CSCs, one must devastate the root (CSCs) to kill a tree (tumors), or else it will resurge. [ 5 ] However, emerging evidence also revealed that non‐CSCs can transform to CSCs fueled by some intrinsic and extrinsic factors and the dynamic interconversion throughout tumorigenesis obviously contributes to the tumor heterogeneity and failure of treatments. [ 6 ] In recent years, it thus reaches a consensus that inhibiting the growths of CSCs together with destroying differentiated tumor cells are both necessary for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis has been backed up by the identification of CSCs in a growing and diverse group of tumors. This has motivated the search for new therapeutic paradigms based on the idea that the incapacitation of the CSCs, with the simultaneous use of conventional therapies to reduce the DCC load, is the most effective procedure to control tumor growth [5,13,3,14,15]. One possible therapeutic course to eliminate the CSC component is to induce CSC differentiation.…”
Section: Introductionmentioning
confidence: 99%